Development, beneficial effects, and economic viability of rice straw and paddy husk composts in combination with clinoptilolite zeolite - Omar, Latifah (2016)
Indiscriminate uses of nitrogen (N) fertilizers lead to low N use efficiency and losses through runoff, leaching, denitrification, and volatilization resulting in a series of environmental problems. Clinoptilolite zeolite and composts derived from agricultural wastes could be used to improve N use efficiency by adsorbing NH4 + ions from urea and desorbing them timely for Zea mays L. (test crop) use because the clinoptilolite zeolite, rice straw, and paddy husk composts have high affinity for NH4 + ions. Thus, the objectives of this study were to: (i) produce composts through co-composting of rice straw and paddy husk with chicken slurry amended with clinoptilolite zeolite; (ii) improve N availability by retaining exchangeable NH4 + through the use of clinoptilolite zeolite, rice straw, and paddy husk composts; (iii) determine the use of clinoptilolite zeolite, rice straw, and paddy husk composts in improving N use efficiency and grain yield of Zea mays L. cultivation on a tropical acid soil; and (iv) determine the economic viability of using combination of inorganic fertilizers, clinoptilolite zeolite, rice straw, and paddy husk composts in Zea mays L. cultivation on a tropical acid soil. Rice straw compost was produced by mixing 20 kg of rice straw + 1 kg of chicken feed + 1 kg of molasses + 1 kg clinoptilolite zeolite + 1 kg urea + 13 L chicken slurry in five polystyrene boxes and these ratios apply to mixture of paddy husk too. Mature composts with good agronomic properties, dark brown, soft, coarse with friable texture, and earthy smell were produced by co-composting rice straw and paddy husk with chicken slurry and clinoptilolite zeolite as additives. Soil leaching and incubation studies were conducted for 30 and 90 days, respectively, to determine the effects of amending urea with clinoptilolite zeolite, rice straw and paddy husk composts on controlling NH4 + and NO3 - losses from urea. Urea amended with clinoptilolite zeolite, rice straw and paddy husk composts significantly controlled NH4 + and NO3 - release from urea (soil leaching and incubation studies) compared with urea alone, thus reducing leaching of NH4 + and NO3 -. Ammonium and NO3 - leaching losses during the 30 days of leaching and 90 days of incubation were highest in urea alone compared with urea amended with clinoptilolite zeolite, rice straw, and paddy husk composts treatments. The higher adsorption and lower desorption of NH4 + in soils with clinoptilolite zeolite, rice straw, and paddy husk composts corroborated the ability of clinoptilolite to be used as NH4 + adsorbent and rice straw and paddy husk composts as NH4 + bio-adsorbent. The high buffering capacities of rice straw and paddy husk composts ensured higher rate of NH4 + adsorption. Combined use of urea, clinoptilolite zeolite, rice straw, and paddy husk composts improved soil total N, exchangeable NH4 +, and available NO3 - compared with urea alone. Soil total hydrolyzable N, NH4-N, (NH4 + + amino sugar)-N, amino sugar-N, and amino acid-N soils were higher in soils with clinoptilolite zeolite, rice straw, and paddy husk composts compared with urea alone suggesting mineralization of N into available forms of N (NH4 + and NO3 -) was affected by the addition of clinoptilolite zeolite, rice straw, and paddy husk composts. Urea can be amended with clinoptilolite zeolite, rice straw, and paddy husk composts to regulate availability N for optimum crops use. Promising treatments from the soil leaching and incubation studies were tested in a pot study using Zea mays L. Thai super sweet hybrid F1 (test crop) under controlled environment. At 45 days after planting (tasseling stage of Zea mays L.), amending inorganic fertilizers with clinoptilolite zeolite, rice straw and paddy husk composts increased soil total N, exchangeable Ca, Mg, K, and available P. Uptake and use efficiency of P and K of Zea mays L. were significantly improved upon amending inorganic fertilizers with clinoptilolite zeolite, rice straw and paddy husk composts. The treatments in the pot study were further tested in a field trial. A field trial was conducted for 72 days (maturity period of Zea mays L.) for two consecutive planting cycles of Zea mays L. Amending urea with clinoptilolite zeolite, rice straw, and paddy husk composts improved N use efficiency because of temporary adsorption of exchangeable NH4 + on the negative charge sites of the clinoptilolite zeolite and organic matter of the rice straw and paddy husk composts. As a result, N use efficiency and grain yield of Zea mays L. were increased. The use of inorganic fertilizers, clinoptilolite zeolite, rice straw, and paddy husk composts also enhanced timely uptake of P, K, Ca, Mg, and Na in the aboveground biomass of Zea mays L. compared with the conventional use of inorganic fertilizers alone. The higher retention of N, P, K, Ca, Mg, and Na in the soil regardless of the planting cycle of Zea mays L. suggests build-up of these nutrients in the soil. This is partly responsible for the higher fresh cobs yield of the Zea mays L. in the plots with inorganic fertilizers, clinoptilolite zeolite, rice straw, and paddy husk composts compared with inorganic fertilizers only. A follow up laboratory study on the field trials was conducted to determine the effects of clinoptilolite zeolite, rice straw, and paddy husk composts on decomposition of soil N fractions. Clinoptilolite zeolite, rice straw, and paddy husk composts increased total hydrolyzable N, NH4-N, (NH4 + + amino sugar)-N, amino sugar-N, and amino acid-N compared with urea alone suggesting the clinoptilolite zeolite, rice straw, and paddy husk composts increased N availability by gradually hydrolyzing NH4 + and timely mineralizing NH4 + for Zea mays L. use. The higher (NH4 + + amino sugar)-N, amino sugar-N, and amino acid-N in the soil with clinoptilolite zeolite, rice straw, and paddy husk composts amendment were significantly affected by the higher soil total hydrolyzable N and NH4-N following application of clinoptilolite zeolite, rice straw, and paddy husk composts. Combined application of inorganic fertilizers, clinoptilolite zeolite, rice straw, and paddy husk composts did not only improved soil total N availability and N use efficiency but it also increased P, K, Ca, Mg, and Na availability, uptake, and use efficiency of these nutrients. Besides, the combination of inorganic fertilizers, clinoptilolite zeolite, rice straw, and paddy husk increased grain yield of Zea mays L. Economic assessment study of using clinoptilolite zeolite, rice straw, and paddy husk composts showed higher total costs production of using these amendments in maize cultivation compared with inorganic fertilizers only. The lower total production costs associated with conventional practice with lower gross revenue and net revenue are relates to the use of inorganic fertilizers only. However, higher maize yield, net revenue, and benefit-cost ratio were obtained for the combined use of inorganic fertilizers, clinoptilolite zeolite, rice straw, and paddy husk composts in Zea mays L. cultivation and thus, suggest economic viability of including clinoptilolite zeolite, rice straw, and paddy husk composts.